Effects of private health insurance on medical expenditure and health service utilization in South Korea: a quantile regression analysis - Kristine Namhee Kwon; Wankyo Chung (BMC, 2023)
Abstract Background Despite universal health insurance, South Korea has seen a sharp increase in the number of people enrolled in supplemental private health insurance (PHI) during the last decade. This study examined how private health insurance enrollment affects medical expenditure and health service utilization. Methods Unbalanced panel data for adults aged 19 and older were constructed using the 2016-2018 Korea Health Panel Survey. Quantile regression for medical cost, and quantile count regression for health service utilization were utilized using propensity score-matched data. We included 17 variables representing demographic, socioeconomic, and health information, as well as medical costs and use of outpatient and inpatient care. Results We discovered that PHI enrollees' socioeconomic and health status is more likely to be better than PHI non-enrollees'. Results showed that private health insurance had a greater effect on the lower quantiles of the conditional distribution of outpatient costs (coefficient 0.149 at the 10th quantile and 0.121 at the 25th quantile) and higher quantiles of inpaitent care utilization (coefficient 0.321 at the 90th quantile for days of hospitalization and 0.076 at the 90th quantile for number of inpatient visits). Conclusions PHI enrollment is positively correlated with outpatient costs and inpatient care utilization. Government policies should consider these heterogeneous distributional effects of private health insurance.